Delighting to Preach: Teaching Towards Affective Formation (Homiletic, 2024)
Learning to preach is an activity of holistic formation involving a student’s intellect, behavior, and emotions. Yet it is this last component – affective formation – that often proves most difficult to address in a required preaching course. How does one form student affections for preaching so that they come to delight in the practice when they only take the course as a requirement? What does it mean to teach in ways that aim at affective formation? What activities can students do to demonstrate formation of the affections? This paper draws on Jonathan Edwards’s account of the religious affections to develop strategies for affective formation within the context of a preaching course. It reflects on one pedagogical strategy used by the author for teaching toward affective formation in preaching courses. Overall, this article seeks to foster a conversation on the importance of affective formation for preaching and pedagogical strategies for bringing it about.